Answer :

Let f(x) =

By product rule

f’(x) = na (cx + d)m (ax + b)n-1 + mc (ax + b)n (cx + d)m-1

f’(x) = (ax + b)n-1 (cx + d)m-1 [na (cx + d) + mc (ax + b)]

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

<span lang="EN-USMathematics - Exemplar

<span lang="EN-USMathematics - Exemplar